Numbers 1-19 - Morales, L. Michael (Apollos Old Testament commentary, 2024)
"Often overlooked and regularly misunderstood, the Book of Numbers is a daunting prospect for scholars, preachers and students. It covers part of the Israelites' wilderness years between Egypt and the land of the promise - seemingly very different to and detached from our modern context. Yet God's covenant love remains the same, and the book of Numbers remains extremely relevant for ecclesiology and for the church's life within the already-not yet of the present 'wilderness' era. In his magisterial new commentary, Morales carefully demonstrates the ongoing relevance of Numbers, it's positive vision for life and the surprising challenge it offers to contemporary Christians. This detailed and comprehensive commentary sheds fresh light on a part of the Bible often referenced yet rarely preached and explained. Within this commentary on Numbers 1-19, Form and Structure sections examine the context, source-critical and form-critical issues and rhetorical devices of each passage. Comment sections offer thorough, detailed exegesis of the historical and theological meaning of each passage, and Explanation sections offer a full exposition of the theological message within the framework of biblical theology and a commitment to the inspiration and authority of the Old Testament." --